THE IMPACT OF PERFORMANCE APPRAISAL, REWARD SYSTEM, JOB STRESS, AND WORK LIFE CONFLICT TO EMPLOYEE PERFORMANCE - Rumambie, Yuliana Fransisca (Universitas Sam Ratulangi, 2014)
Employee Performance is an important part in a company or organization. It plays a very important role in an organization because performance of the company or organization largely depends on the performance of its employee. Recently, organizations realize that there are several factors that can affect employee performance. Several factors that can considered as the major determinants of employee performance, such as Performance Appraisal, Reward System, Job Stress, and Work life conflict. The relationship between Performance Appraisal, Reward System, Job Stress, and Work life conflict, is researched using Multiple Regression Analysis. The data gathered by questionnaire that spread among fifty employees at Kantor Dinas Perhubungan Provinsi Sulawesi Utara.Â The finding from the current study stated that there is a positive relationship between performance appraisal, reward system, job stress, work life conflict, and employee performance. The most influencing factor is reward system. This research using convenience sampling refers to the collection of information from members of the population who are conveniently available to provide it. Convenience sampling is most often used during the exploratory phase of a research project and is perhaps the best way of getting some basic information quickly and efficiently. Keywords: employee performance, performance appraisal, reward system, job stress, and work life conflict.